Composición, variación anual y estacional de la dieta de Teius suquiensis (Sauria: teiidae) en la provincia de Córdoba (Argentina) - Ávila, Luciano Javier (1992)
The stomachs of 109 parthenogenetic lizards of the genus Teius of the Valley of Punilla, Córdoba, Argentina, were analized to evaluate the composition and seasonal variation during the summers of 1988-1989 and 1989-1990. After the analysis, diet categories were established and frequency, volumen and the number of items consumed. The IR., Relative Index of Importance was used and the Termites, Beetles, Larvae, and Grasshoppers were the principal components of the diet.